Do teachers believe they are competent to promote ICT use among their students? - Zlamanski, R.; Ciccarelli, Marina (IOS Press, 2012)
Background: Information and communication technologies (ICT), including computers, are becoming commonplace tools for learning by school children in Australia and around the world. Teachers are responsible for integrating ICT into the school learning environment; however, they may not recognize how and when ICT use may compromise their students’ physical health. Children’s exposure to physical harm through the unhealthy use of ICT may have liability implications for the education sector. Objectives: To determine (i) whether teachers consider it their responsibility to promote healthy ICT use among their students; (ii) teachers’ self-perceived competence to do so; and (iii) what teachers perceive are the barriers and enablers to promoting healthy ICT use among their students. Method: An online survey was developed for the study. All Catholic Education school principals in Western Australia (n=157) were sent an email link to the survey for distribution to teachers at their respective schools. Over the three week survey period, 95 teachers completed the survey. Descriptive and inferential statistics were used to analyze the data and summarize participants’ responses.Results: Fifty-five percent of teachers agreed they were concerned about their students’ physical health when using ICT. Only 19% of teachers reported they frequently or always provided their students with information on how to use computers in their class in a way, so as to promote physical health. Teachers identified barriers to promoting healthy computing use among students including; insufficient time (47%), non-adjustable furniture (46%), and insufficient knowledge (41%). Male teachers reported more confidence in their ability to promote healthy ICT use among students than female teachers. Conclusion: Just over half of the teachers in this study were concerned for the physical health of their students when using ICT in the classroom. Respondents identified barriers that limit their ability to promote healthy practices to their students. Designing and implementing school-based computer ergonomics education programmes may assist teachers fulfil their duty of care in regard to the physical health and well-being of their students.